(untitled) (Faridpur Medical College Journal, 2017)
Iron deficiency is the most common nutritional deficiency state of women in childbearing age. Peri-partum iron deficiency anaemia (IDA) is associated with significant maternal, fetal and infant morbidity. An effective management is needed to prevent adverse outcomes. Current options for treatment are limited; these include oral iron supplements, which are usually ineffective and poorly tolerated, and whole blood transfusion, which carries an inherent risk, should be avoided during pregnancy. Intravenous ferric carboxymaltose is a new treatment option and it is better tolerated with a good result. The study was designed to assess the safety and efficacy of intravenous ferric carboxymaltose for correction of IDA in pregnant women in third trimester. It was a prospective study; 260 anaemic pregnant women received Injection ferric carboxymaltose, as a total dose of 500-1000 mg between 28 to 36 weeks of pregnancy. Safety was assessed by analyzing adverse drug reactions. Ferric carboxy maltose significantly increased Hb level (p<0.001) in all women in this study group. Increased Hb value was observed 3-4 weeks after infusion. None of the women felt worse. No serious adverse effects were found and minor side effects occurred in 34(13%) patients.Our study revealed that the Hb level increased significantly, was well tolerated and without significant side effects. Faridpur Med. Coll. J. Jul 2017;12(2): 54-57